Analysis of trio test in neurodevelopmental disorders - Kim, Se Hee; Kwon, Soon Sung; Lee, Joon Soo; Kim, Heung Dong; Lee, Seung-Tae; Choi, Jong Rak; Shin, Saeam; Kang, Hoon-Chul (Frontiers in Pediatrics, 2022)
Background Trio test has been widely used for diagnosis of various hereditary disorders. We aimed to investigate the contribution of trio test in genetically diagnosing neurodevelopmental disorders (NDD). Methods We retrospectively reviewed 2,059 NDD cases with genetic test results. The trio test was conducted in 563 cases. Clinical usefulness, optimal timing, and methods for the trio test were reviewed. Results Pathogenic or likely pathogenic variants were detected in 112 of 563 (19.9%) patients who underwent the trio test. With trio test results, the overall diagnostic yield increased by 5.4% (112/2,059). Of 165 de novo variants detected, 149 were pathogenic and we detected 85 novel pathogenic variants. Pathogenic, de novo variants were frequently detected in CDKL5, ATP1A3, and STXBP1. Conclusions The trio test is an efficient method for genetically diagnosing NDD. We identified specific situations where a certain trio test is more appropriate, thereby providing a guide for clinicians when confronted with variants of unknown significance of specific genes.